PENGEMBANGAN POSTER MENGENAI AKTIVITAS ANTIBAKTERI SARI PATI DAUN PEPAYA (Carica papaya L) Terhadap Escherichia coli UNTUK MASYARAKAT - Nopa Nopiyanti; Destien Atmi Arisandy; Linna Fitriani (Jurnal Penelitian Pendidikan IPA, 2026)
In recent years, the use of natural ingredients as antibacterial agents has gained increasing attention due to the increasing antibiotic resistance. One such potential is papaya leaf extract (Carica papaya L.), which has shown antibacterial activity against Escherichia coli, a common cause of diarrhea in the community. This study aims to develop an educational poster that communicates the antibacterial benefits of papaya leaf extract against Escherichia coli. This study used the Research and Development (R&D) model as modified by Borg & Gall, which consists of five stages: (1) initial information collection, (2) planning, (3) initial product development, (4) limited field testing, and (5) product revision. Validation was carried out by material, media, and language experts, while readability testing was conducted on individuals aged ≥17 years. Data analysis included qualitative content analysis and quantitative descriptive analysis to evaluate the feasibility and readability of the poster. The results showed that the developed poster obtained a validation score above 80% from all experts, and a highest readability score of 95% from the community, indicating that the poster was very feasible, informative, and easy to understand. The strength of the poster lies in its attractive visual design, communicative language, and concise and focused content. This educational media is expected to increase public awareness of diarrhea prevention using herbal plants. Further research is recommended to explore the long-term impact of the media on behavioral change and assess the antibacterial effectiveness of papaya leaf extract in various formulations.